An exploration of the relationship between recruitment communication and foraging in stingless bees. Issue 5 (12th May 2021) - I'Anson Price, Robbie; Segers, Francisca; Berger, Amelia; Nascimento, Fabio S; Grüter, Christoph
Abstract: Social information is widely used in the animal kingdom and can be highly adaptive. In social insects, foragers can use social information to find food, avoid danger, or choose a new nest site. Copying others allows individuals to obtain information without having to sample the environment. When foragers communicate information they will often only advertise high-quality food sources, thereby filtering out less adaptive information. Stingless bees, a large pantropical group of highly eusocial bees, face intense inter- and intra-specific competition for limited resources, yet display disparate foraging strategies. Within the same environment there are species that communicate the location of food resources to nest-mates and species that do not. Our current understanding of why some species communicate foraging sites while others do not is limited. Studying freely foraging colonies of several co-existing stingless bee species in Brazil, we investigated if recruitment to specific food locations is linked to 1) the sugar content of forage, 2) the duration of foraging trips, and 3) the variation in activity of a colony from 1 day to another and the variation in activity in a species over a day. We found that, contrary to our expectations, species with recruitment communication did not return with higher quality forage than species that do not recruit nestmates. Furthermore, foragers from recruiting species did not have shorter foraging trip durations than those from weakly recruiting species. Given the intense inter- and intraspecific competition for resources in these environments, it may be that recruiting species favor food resources that can be monopolized by the colony rather than food sources that offer high-quality rewards.